Optimal number and discharge rate of emitters for coconut palm in sandy loam soil - Priya Nair G (Department of Irrigation and Drainage Engineering, Kelappaji College of Agricultural Engineering and Technology, 2000)
AgricullurClI productivity is based on the availability of required water at proper time. As water is becoming Cl limited resource its efficient utilization is very essential. The distribution of rainfall in Kcrala is not adequate to meet the total welter requirement of coconut. Coconut in Kerala are mostly grown in sandy soils which has a poor water holding capacity. So drip irrigation is the best method of irriqation for coconut in this soil. The efficient design of drip irrigation system involves the optimal spacing of emitters, correct discharge rate anr' duration of inigc\lion based on the movement of soil moisture front. So the study of moisture distribution pattern under chip irriU(ltion is helpful in deciding optimum number and discharge rate of emitters and duration of irriqation required for coconut palms The study was conducted in the river side coconut gc)rdr.n of the instruclional Farm, I~CAET, TaVilrH1I. The size of the plot was 28x63m. The soil properties viz texture. bulk dcn-itv. infiltration rate, field capacity. hydraulic conductivity and permanent \vi!;JI1q point were observed. The drip system was installed in the fielc! Two different c!ischarge rates (4 and 8lph) and three f combination of number of emitters (3,<'1 & 6) were selected for the study. The maximum vertical and horizontal advance of soil moisture front for both the discharge rates (4 and 8 Iph) were noted. Empirical equations were also developed for both vertical and horizontal advance. The soil moisture contents were determined at different horizontal anc! vertical distances from the emitter, before irriqation, 1 hour, 24 hours and 3 days after irrigation by gravimetric method. The soil moisture contour maps were plotted and the moisture distribution efficiency was calculated for each treatment at all depths. The maximum vertical and horizontal advance was observed for 8 lph emitter compared to 4 Iph emitter. The welting front from a single emitter produced C\ bulb like \Netting pattern for both the discharges. The size of the wetting bulb increased with increase in discharge rate. The study revealed that 4 numbers of 8 Iph emitters give more uniform distribution compared to all the other treatments.